DIGITAL TWINS IN SCULPTURE STUDIOS: ENHANCING LEARNING - Dhabliya, Dharmesh; Patkar, Uday Chandrakant; Yadav, Pooja; Tonpe, Ketan Kishor; Gandhi, Yatin; Rajashri CK (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The expanding penetration of computational technologies into the studio-based education has provided new possibilities to improve learning in long-standing traditionally material-centered fields like sculpture. The current paper examines the application of digital twin technology as a facilitating model of hybrid physical-digital sculptural pedagogy. The concept of a digital twin-powered sculpture studio is envisioned as a closed-loop system connecting the actual making conditions with the virtual simulation in real-time and the feedback directed towards learners. The suggested framework combines sensing infrastructure, physics-based and parametric simulation, the analytics which is supported by the artificial intelligence and the interactive visualization interfaces to facilitate the iterative exploration, predictive reasoning, and reflective practice. It describes a modular system architecture, which is the interaction between physical studio components, digital twin computation and learning analytics layers. The pedagogical assimilation of the system holds major sculptural learning goals of material learning, structural reasoning, and creative problem solving to measurable assurance measures. The viability and didactic value of the method has been shown in a case study carried out in an undergraduate sculpture studio. The empirical results show that students using the digital twin did more virtual cycles before they started doing physical ones, which led to a decrease in physical rework, smaller prediction-execution gap, better resource use in materials, and high-quality sculptural work. The results indicate that digital twins can be used to supplement, and not substitute embodied sculptural practice, by visualizing the otherwise invisible phenomena and enabling evidence-based creative design decisions. The research will add a validated theoretical framework, a system architecture to be implemented and empirical evidence of the pedagogical usefulness of digital twins in creative education. Potential further implications involve immersive visualization and AI-assisted personalization and inter-domain interdisciplinary implementation in the field of studio-based learning.